Combating Counterfeit Medicines: A Case Study of the Egyptian Pharmaceutical Traceability System - Ahmed Abdelfatah, Nourhan Yasser (AUC Knowledge Fountain, 2023)
Counterfeit medicines are a global challenge that has attracted the attention of many authorities in recent years. The problem worsened dramatically, causing adverse public health impacts and significant financial repercussions. Many countries, including Egypt, have attempted to adopt pharmaceutical track-and-trace systems to secure supply chains. Despite the significance of the problem, only a few scholars have studied the topic in Egypt. This qualitative study seeks to bridge the research gap and provide a clearer picture of counterfeit medicines in the Egyptian context. In addition, it aims to understand the role of the Egyptian Drug Authority and the policy motivations behind the Egyptian government's decision to launch a pharmaceutical traceability system. To achieve this goal, the study examined the pilot implementation of the project, focusing on success factors and challenges that policymakers need to address. Three cohorts were targeted for semi- structured in-depth interviews: supply chain stakeholders, organizations involved in policy implementation, and independent experts. This study found that improving patient safety, combating counterfeit medicines, managing logistics and inventories, and preventing reimbursement fraud were the main drivers for adopting the Egyptian pharmaceutical traceability system. Even though stakeholders encountered technical and financial issues during the pilot implementation attempts, they all agreed that this system was advantageous. Based on the experiences of other countries and according to the Egyptian context, the study put recommendations forward to help establish a successful national pharmaceutical traceability project. They included establishing harmonized policies and regulations, offering incentives to pharmaceutical companies, promoting awareness and education, and promoting collaboration among various stakeholders. Finally, when Egypt can modify the system in response to stakeholder needs, it will successfully implement the pharmaceutical track and trace system and witness a significant revolution in the supply chain.